Creatine supplementation--Part II: in vivo magnetic resonance spectroscopy - Kreis, R.; Kamber, M.; Koster, M.; Felblinger, J.; Slotboom, J.; Hoppeler, H.; Boesch, C. (Medicine & Science in Sports & Exercise, 1999)
Purpose: Our purpose was to study effects of creatine (Cr) supplementation on muscle metabolites noninvasively by means of magnetic resonance spectroscopy (MRS) before and after supplementation with Cr or placebo. Methods: 1H-MRS was used in a comprehensive, double-blind, cross-over study in 10 volunteers to measure Cr in m. tibialis anterior and m. rectus femoris at rest. PCr/ATP was observed in m. quadriceps femoris by 31P-MRS at rest and after exercise. Results: A significant increase in total Cr was observed with Cr intake in m. tibialis anterior (+9.6 ± 1.7%, P = 0.001) and in m. rectus femoris (+18.0 ± 1.8%, P < 0.001). PCr/ATP showed a significant increase (+23.9 ± 2.3%, P < 0.001) in m. quadriceps femoris at rest with Cr supplementation. Post-Cr supplementation recovery rates from exercise were significantly lower (k = 0.029 s-1, P < 0.01) compared with postplacebo consumption (k = 0.034 s-1) and presupplementation (k = 0.037 s-1). However, higher levels of PCr/ATP at rest compensate for this reduction of the recovery rate after Cr supplementation. The increase of PCr/ATP determined by 31P-MRS correlates with the increase of Cr observed by 1H-MRS (r = 0.824, P < 0.001). Conclusion: Noninvasive observation of Cr and PCr after Cr supplementation shows an increase in a muscle specific manner. Higher preexercise levels of PCr/ATP at rest compensate for significantly slower recovery rates of PCr/ATP after Cr supplementation. (see also http://www.baspo.ch/d/wissen/publikat.htm#creatin2)